Movilidad de las representaciones del modelo sol-tierra-luna: estrategia didáctica para estudiantes de quinto de primaria - Menjura Gonzalez, Maritza; Ochoa Cárdenas, Mónica Jhoanna; Malangón, Rusby; Tuay, Nidia (Revista Científica, 2011)
In the field of science education, astronomy has been a topic of great interest, which has served as a bridge between the individual man ́s taste by natural phenomena and scientific knowledge. Therefore this paper seeks to take advantage of the curiosity aroused in children by the celestial bodies observed daily to put forward the study of the heliocentric model. To achieve this objective, first we identified the representations about the Sun-earth-moon system of the fifth-grade students of the College José Martí IED, in order to design a teaching strategy that facilitates the mobility of these representations, to guide them or to strength them for the understanding of the heliocentric model, based on a study of the phases of the moon. This research paper begins by recognizing the students of elementary school as young explorers equipped with the skills to explain with arguments the world around them. This strategy pretends to favor the construction of scientific concepts which later will become a link that will promote the learning of science in academic processes.